2013
DOI: 10.4028/www.scientific.net/amr.634-638.245
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Behaviors of Chemical Components from Steel Slag

Abstract: The leaching characteristics of chemical components from converter steel slag were studied through circulating leaching experiments. Results show that the most quality of leaching is CaO, SiO2 is the second and Al2O3 is the least. Analyzing the leaching process and experimental results, it can conclude that the leaching kinetics is controlled by intra-paticle diffusion. The leaching process can be described by shrinking unreacted core model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Possible reactions between slag components and simulated AMD (0.1 M H 2 SO 4 ) were listed in Table 2. The related Gibbs free energy changes for the reactions indicated that the reaction sequence of components with simulated AMD was CaO > MgO > FeO > C 2 S > C 2 F > C 3 S under room temperature [12]. However, some synthetic pure Ca-and Mg-bearing minerals studied by leaching experiments and thermodynamic analysis thought that the leaching order for different phases is CaO > (Ca…”
Section: Phase Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible reactions between slag components and simulated AMD (0.1 M H 2 SO 4 ) were listed in Table 2. The related Gibbs free energy changes for the reactions indicated that the reaction sequence of components with simulated AMD was CaO > MgO > FeO > C 2 S > C 2 F > C 3 S under room temperature [12]. However, some synthetic pure Ca-and Mg-bearing minerals studied by leaching experiments and thermodynamic analysis thought that the leaching order for different phases is CaO > (Ca…”
Section: Phase Characteristicsmentioning
confidence: 99%
“…When steel slag was used in unbound and bitumen-bound layers, its acceptable contents of f-CaO and f-MgO should be lower than 7% and 4% [5]. Therefore, it is necessary to promote the steel slag utilization ratios alternatively, such as soil remediation [12], water treatment [13][14][15][16][17], AMD neutralization [9,10] and other promising pollution control applications.…”
Section: Introductionmentioning
confidence: 99%